A near-infrared fluorescent probe for accurately diagnosing cancer by sequential detection of cysteine and H+. Issue 39 (16th April 2021) - She, Zun-Pan; Wang, Wen-Xin; Mao, Guo-Jiang; Jiang, Wen-Li; Wang, Zhi-Qing; Li, Yongfei; Li, Chun-Yan
Abstract : A near-infrared fluorescent probe, CyAc, is synthesized for accurately diagnosing cancer in vivo by sequential detection of Cys and H + . CyAc can not only discriminate normal cells and cancer cells, but also distinguish normal mice from tumor mice. Abstract : A near-infrared fluorescent probe, CyAc, is synthesized for accurately diagnosing cancer in vivo by sequential detection of Cys and H + . CyAc can not only achieve a good distinction between normal cells and cancer cells, but also distinguish normal mice from tumor mice.